# there are 2 proving identities problem that i cannot solve 1. CosecA-secA/cosecAsecA =cosA-sinA 2 sin^2A-tanA/cos^2A-cotA = sec^2A-1 Thankyou for helping me!!

*print*Print*list*Cite

### 1 Answer

1.) Simplify the equation first,

Left hand side = (cosecA-secA)/cosecA secA = (cosecA/cosecAsecA) - (secA/cosecAsecA)

= 1/secA - 1/cosecA

using the identity, sec A = 1/cosA and cosecA = 1/sinA, we get

LHS= 1/secA - 1/cosecA = 1/(1/cosA) - 1/(1/sinA) = cosA-sinA = RHS. Hence proved.

2) simplify everything in terms of sin and cos, using tanA = sinA/cosA and cotA = 1/tanA

LHS = (sin^2A-tanA)/(cos^2A-cotA) = (sin^2A - sinA/cosA)/(cos^2A - cosA/sinA)

= [(sin^2A cosA-sinA)/cosA]/[(cos^2AsinA-cosA)/sinA] = [(sinA/cosA)x(sinAcosA-1)]/[(cosA/sinA)x((cosAsinA-1)] = (sinA/cosA)/(cosA/sinA) ,after cancelling out (sinAcosA-1) from both numerator and denominator.

LHS = sin^2A/cos^2A = (1-cos^2A)/cos^2A = 1/cos^2A - 1 = sec^2A -1= RHS

Hence proved.